Respuesta :
Answer:4(x - 1) - x = 3(x + 5) - 11
Step-by-step explanation:
Lily's work:
4(x – 1) – x = 3(x + 5) – 11
4x – 4 – x = 3x + 15 – 11
3x – 4 = 3x + 4
Her partial solution, 3x - 4 = 3x + 4, can be interpreted as a FALSE statement because 3x - 4 does NOT equal 3x + 4.
Since it is a false statement, the equation has no solution.
The number of the solution will be infinity. Then the correct option is D.
What is the solution of the equation?
The solution of the equation means the value of the unknown or variable.
The equation is given below.
4(x – 1) – x = 3(x + 5) – 11
Simplify the equation, we have
4x – 4 – x = 3x + 15 – 11
3x - 3x = 8
The variable x is eliminated.
Then the number of the solution will be infinity.
Then the correct option is D.
More about the solution of the equation link is given below.
https://brainly.com/question/545403
#SPJ2